Development a novel design of miniaturized heptagonal Koch fractal wide band antenna for 5G mm wave and IoT applications - Kassym, Ruslan; Balgynbek, Turdybek; Serikov, Tansaule; Ahmetova, Patam; Sergazin, Gani; Ozhikenov, Kasymbek; Sultangaziyev, Tanirnazar; Kumar, Pramod; Tlenshiyeva, Akmaral; Yernazarov, Nursultan (Eastern-European Journal of Enterprise Technologies, 2024)
The object of the study is a compact heptagonal broadband antenna specially designed for use in the 5G millimeter band using Koch fractals to improve performance. As a result of the study, the most important problem of achieving higher gain, improving bandwidth and reducing interference at higher frequencies, which is necessary for the effective functioning of 5G networks, was solved. As a result, the maximum realized gain of 5 dB was obtained at a frequency of 27.58 GHz with an impressive bandwidth in the range from 26.5 to 40 GHz. The use of Koch fractal geometry and defective ground planes significantly improves impedance matching and expands bandwidth, which explains the excellent antenna performance compared to traditional designs. The features and distinguishing features of the results obtained, thanks to which they allowed solving the problem under study, are its compact dimensions (only 9 mm by 9 mm) and the ability to maintain VSWR at a level of less than 2 in the entire frequency spectrum. These features make the antenna particularly suitable for millimeter-band integration and flexible applications such as portable devices and wearable home appliances. The field of practical application of the results includes integration into portable and wearable devices, improving the performance and connectivity of Internet of Things applications. The conditions of practical use require compliance with 5G network standards and compatibility with millimeter-wave technologies. This characterizes the antenna as a significant achievement in antenna technology, demonstrating its potential for widespread adoption in next-generation wireless communication systems and paving the way for more reliable and high-performance wireless networks